PTHR1 polymorphisms influence BMD variation through effects on the growing skeleton. - Vilariño-Güell, C; Miles, L; Duncan, E; Ralston, S; Compston, J; Cooper, C; Langdahl, B; Maclelland, A; Pols, H; Reid, D; Uitterlinden, A; Steer, C; et al. (2007)
We investigated whether polymorphisms in PTHR1 are associated with bone mineral density (BMD), to determine whether the association of this gene with BMD was due to effects on attainment of peak bone mass or effects on subsequent bone loss. The PTHR1 gene, including its 14 exons, their exon-intron boundaries, and 1,500 bp of its promoter region, was screened for polymorphisms by denaturing high-performance liquid chromatography (dHPLC) and sequencing in 36 osteoporotic cases. Eleven single-nucleotide polymorphisms (SNPs), one tetranucleotide repeat, and one tetranucleotide deletion were identified. A cohort of 634 families, including 1,236 men (39%) and 1,926 women (61%) ascertained with probands with low BMD (Z< -2.0) and the Children in Focus subset of the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort (785 unrelated individuals, mean age 118 months), were genotyped for the five most informative SNPs (minor allele frequency >5%) and the tetranucleotide repeat. In our osteoporosis families, association was noted between lumbar spine BMD and alleles of a known functional tetranucleotide repeat (U4) in the PTHR1 promoter region (P = 0.042) and between two and three marker haplotypes of PTHR1 polymorphisms with lumbar spine, femoral neck, and total hip BMD (P = 0.021-0.047). This association was restricted to the youngest tertile of the population (age 16-39 years, P = 0.013-0.048). A similar association was found for the ALSPAC cohort: two marker haplotypes of SNPs A48609T and C52813T were associated with height (P = 0.006) and total body less head BMD (P = 0.02), corrected for age and gender, confirming the family findings. These findings suggest a role for PTHR1 variation in determining peak BMD.